Cranial modification and trepanation in pre-Hispanic collections from Peru in the Museum of Anthropology and Ethnology, Florence, Italy. - Mori, Tommaso; Riga, Alessandro; Dionisio, Giulia; Bigoni, Francesca; Moggi-Cecchi, Jacopo (Medicina Historica, 2022)
Artificial cranial modification (ACM) and trepanation are medical treatments with a long history among different human societies. One of the most iconic cultures, Pre-Hispanic Peruvian populations, are well known for evidence of ACM and trepanation. Here, we present evidence of such practices from the collection housed in the Museum of Anthropology and Ethnology, University of Florence, Italy. The Museum has a rich and important collection of medical-related specimens such as instruments and human remains. We studied the presence of ACM and trepanation in 370 skulls, from different regional and cultural periods, and medical tools. Most of the osteological remains came from the Lima region and Cuzco. Frequencies of ACM and trepanation were compared to evaluate differences in their occurrence in the two regions and among sexes and age groups. Among the 287 skulls with ACM these were distributed similarly in all age classes; no differences between sexes were found. Lima and Cuzco samples differed strongly for the type of ACM, with the first showing tabular type and the second the annular one. Trepanation was documented by 14 specimens mainly from Cuzco. Most of the individuals survived the trepanation events. Trepanation was achieved using two methods: scarification and circular cutting. From the ethnological collection, a total of 16 instruments used in the process were described and studied. Chisels were found as funerary belongings, thus indicating the importance such tools had for these populations and the association between medical treatments and magical and religious rituals. This evidence confirmed the specialized knowledge and advanced medical practices that Pre-Hispanic populations had.